2015
DOI: 10.2174/1570162x13666150121111548
|View full text |Cite
|
Sign up to set email alerts
|

Didehydro-Cortistatin A Inhibits HIV-1 Tat Mediated Neuroinflammation and Prevents Potentiation of Cocaine Reward in Tat Transgenic Mice

Abstract: HIV-1 Tat protein has been shown to have a crucial role in HIV-1-associated neurocognitive disorders (HAND), which includes a group of syndromes ranging from undetectable neurocognitive impairment to dementia. The abuse of psychostimulants, such as cocaine, by HIV infected individuals, may accelerate and intensify neurological damage. On the other hand, exposure to Tat potentiates cocaine-mediated reward mechanisms, which further promotes HAND. Here, we show that didehydro-Cortistatin A (dCA), an analog of a n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
61
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 62 publications
(64 citation statements)
references
References 92 publications
3
61
0
Order By: Relevance
“…Conceivably, novel therapeutics that target Tat's neuroinflammatory actions may provide protection from subsequent cellular toxicity. One connatural compound, didehydro-Cortistatin A, targets Tat transactivation directly and has been recently shown to attenuate Tatmediated increases in pro-inflammatory cytokines including IL-1β and IL-6 in vitro [40]. The present results suggest that mitigation of Tat's neuroinflammatory processes that disrupt sensorimotor gating via actions in localized brain regions (i.e.…”
Section: Discussionmentioning
confidence: 61%
“…Conceivably, novel therapeutics that target Tat's neuroinflammatory actions may provide protection from subsequent cellular toxicity. One connatural compound, didehydro-Cortistatin A, targets Tat transactivation directly and has been recently shown to attenuate Tatmediated increases in pro-inflammatory cytokines including IL-1β and IL-6 in vitro [40]. The present results suggest that mitigation of Tat's neuroinflammatory processes that disrupt sensorimotor gating via actions in localized brain regions (i.e.…”
Section: Discussionmentioning
confidence: 61%
“…Dox treatment induces Tat protein expression in these mice at concentrations of 0.1–0.9 ng/ml in vitro (48), comparable to cerebrospinal fluid Tat concentrations detected in antiretroviral therapy-treated HIV patients (12). Prior studies of Dox-induced Tat-expressing mice have reported cellular (4855), brain structural (56), and behavioral or cognitive (14,49,50,5255,5760) abnormalities. However, to date, no studies have reported on whether controlled Tat protein expression induces depression-like behavior on tasks commonly used to assess such behavior in mice.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, in the astrocytic cell line U87MG, the Tat-mediated release of the key inflammatory signaling proteins IL-1β, TNF-α, and MCP-1 was reverted by dCA treatment. Finally, using a mouse model that specifically expresses Tat in astrocytes, we demonstrated that dCA reverses the potentiation by Tat of cocaine-mediated reward using conditioned place preference experiments (Mediouni et al 2015). …”
Section: Inhibition Of Extracellular Tatmentioning
confidence: 99%
“…Compounds interacting with the TAR-binding domain of Tat [such as dCA, see Sect. 4.2 (Mousseau et al 2012)] may have the ability to counteract the neurotoxic and cancer-promoting properties of Tat by either reducing its production at the transcription level and by directly inhibiting its pathogenic activity (Mediouni et al 2015). …”
Section: Extracellular Tatmentioning
confidence: 99%
See 1 more Smart Citation